Velocity profile compliance for a wheeled mobile robot - Abdullah, Noor Farahdila (2012)
Mobile robots can be used in many applications, such as exploration, search and rescue, reconnaissance, security, and cleaning. Mobile robots usually carry batteries as their energy source and their operational time is restricted by the finite energy available from the batteries. With great advancements in application of Wheeled Mobile Robots (WMRs), concern of energy grew. Most of (not all) research and work done on the field of robotics is developed with no relation to ‘life’ of the robot. Specially, mobile robots use batteries to power themselves. So, the ‘lifespan’ of these robots is limited. So, the investigations on energy-related concepts are also of great importance. The energy is dissipated mostly in the motors, which strongly depends on the velocity profile. This paper investigates energy efficiency for trapezoidal velocity profile to minimize a new energy object function which considers practical energy consumption dissipated in motors related to motor dynamics, velocity profile, and motor control input. This paper will perform the analyses on energy consumption for trapezoidal velocity profile by using the Pulse Width Modulation (PWM) method as the controller. The goals of this project are by getting the energy optimization and the best velocity profile generation. Through the project, it can be concluded that the main factors in energy optimization based on the velocity profile generation are the election of PWM duty cycle and the time to complete the task. The higher the duty cycle of PWM and the shorter time we gain to complete the task will be result more energy saving in battery consumption. The velocity Profile 3 is chosen as the best velocity profile compared to Profile 1 and Profile 2 in terms of energy efficiency consumption which it gives us 2.48% and 1.95% differences between Profile 1 and Profile 2 respectively.